1.25-0.3k+0.5=1.3+0.5k

Simple and best practice solution for 1.25-0.3k+0.5=1.3+0.5k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.25-0.3k+0.5=1.3+0.5k equation:


Simplifying
1.25 + -0.3k + 0.5 = 1.3 + 0.5k

Reorder the terms:
1.25 + 0.5 + -0.3k = 1.3 + 0.5k

Combine like terms: 1.25 + 0.5 = 1.75
1.75 + -0.3k = 1.3 + 0.5k

Solving
1.75 + -0.3k = 1.3 + 0.5k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-0.5k' to each side of the equation.
1.75 + -0.3k + -0.5k = 1.3 + 0.5k + -0.5k

Combine like terms: -0.3k + -0.5k = -0.8k
1.75 + -0.8k = 1.3 + 0.5k + -0.5k

Combine like terms: 0.5k + -0.5k = 0.0
1.75 + -0.8k = 1.3 + 0.0
1.75 + -0.8k = 1.3

Add '-1.75' to each side of the equation.
1.75 + -1.75 + -0.8k = 1.3 + -1.75

Combine like terms: 1.75 + -1.75 = 0.00
0.00 + -0.8k = 1.3 + -1.75
-0.8k = 1.3 + -1.75

Combine like terms: 1.3 + -1.75 = -0.45
-0.8k = -0.45

Divide each side by '-0.8'.
k = 0.5625

Simplifying
k = 0.5625

See similar equations:

| n-7=22.5 | | -8+x=15 | | -24-2x=11-7x | | .75(x+8)=9 | | 3f+9f-3=7-f | | 69-4x=9x+17 | | 0.5t+4.1=5.7-0.3t | | b+4=7 | | 6x+10=94-6x | | -2(4-x)-7=5 | | 5(x-1)2=50 | | (2x+1)=17 | | 7m-35=5+2m | | (x+1.25)4=12 | | 0=(3x-5)(x-2) | | 6x^7-48x^6+30x^5= | | 7+9x=87+x | | 6h=9 | | 9r-2-6r=1 | | 2x-4=12x-104 | | -32=4c-12 | | 6p-2p=28 | | 75+0.05X=92.40 | | 4x^2+7=23 | | 6d-(4-5d)=-67 | | 26+9x=-1 | | w^2+6w-5=0 | | 3x+8=x+12 | | 3x+28=11x-44 | | 12r-4r=48 | | -6x=54 | | x^2+1.5x+0.5=0 |

Equations solver categories